Incidence, outcome and risk stratification tools for venous thromboembolism in advanced pancreatic cancer – A retrospective cohort study. Issue 157 (September 2017) - Kruger, Stephan; Haas, Michael; Burkl, Carolin; Goehring, Peter; Kleespies, Axel; Roeder, Falk; Gallmeier, Eike; Ormanns, Steffen; Westphalen, Christoph Benedikt; Heinemann, Volker; Rank, Andreas; Boeck, Stefan
Abstract: Introduction: Venous thromboembolism (VTE) is frequent in advanced pancreatic cancer (APC). Recent studies demonstrated that the Khorana score - an established risk stratification tool for VTE in cancer - performs poorly in identifying pancreatic cancer patients at high risk for VTE. Materials and methods: We performed a retrospective cohort study in order to define incidence, treatment and outcome of VTE as well as the performance of VTE risk stratification tools (Khorana score, CONKO score and aPTT ratio) in a "real life" clinical cohort of APC patients undergoing palliative chemotherapy. Results and conclusions: One hundred and seventy-two eligible APC patients from our comprehensive cancer center were identified. VTE after start of palliative chemotherapy was diagnosed in 71 patients (41.3%). Most VTE events were asymptomatic ( n = 50, 29.1%) with only 21 symptomatic events (12.2%). On multivariate analysis - including age, performance status and carbohydrate antigen 19-9 (CA 19-9) - symptomatic VTE was an independent risk factor for death (hazard ratio [HR]: 2.22, 95% CI: 1.05–2.60, p < 0.05). Khorana score, CONKO score and aPTT ratio alone were not able to predict the risk for symptomatic VTE. High risk patients could only be identified by using a combination of either Khorana or CONKO score with aPTT ratio (30% vs. 10% symptomatic VTE events in high vs. low risk patients, p < 0.05). The combination of Khorana or CONKO score with aPTT thus may represent a novel risk stratification tool for symptomatic VTE in APC and should further be validated within prospective clinical trials. Highlights: The addition of aPTT ratio to CONKO or Khorana score may represent a novel tool to identify advanced pancreatic cancer patients at high risk for VTE Optimal management of cancer patients with incidentally diagnosed SVT is controversial. Our data suggests that survival of APC patients is not adversely affected by asymptomatic SVT. Safety of low molecular weight heparin (LMWH) use in APC patients is confirmed in a "real life" clinical setting.